2018
DOI: 10.4049/jimmunol.1701675
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Canonical Notch Signaling Affects Multiple Steps in NK Cell Development in Mice

Abstract: Within the hematopoietic system, the Notch pathway is critical for promoting thymic T cell development and suppressing the B and myeloid lineage fates; however, its impact on NK lymphopoiesis is less understood. To study the role of Notch during NK cell development in vivo, we investigated different NK cell compartments and function in Rbp-Jk fl/fl Vav-Cre tg/+ mice, in which Rbp-Jk, the major transcriptional effector of canonical Notch signaling, was specifically deleted in all hematopoietic cells. Peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…After prenatal hematopoiesis occurs in the fetal liver, the Notch signaling pathway is essential to promote T cell commitment in the thymus and suppress alternative lineage fate potentials, including B cells, DCs, and myeloid cells [126][127][128]. However, some studies suggest that Notch signaling does not restrict NK cell lineage specification [129][130][131]. In the absence of lineage specifying factors, such as Pax5 in B cells or Bcl11 in T cells, pro-B cells or thymocytes can be reprogrammed into NK cells when cultured with Notch ligands (Bcl11 is a target of Notch1 signaling) [132,133].…”
Section: Notch1 Regulates the Generation Of Hscs And Its Commitment Tmentioning
confidence: 99%
See 3 more Smart Citations
“…After prenatal hematopoiesis occurs in the fetal liver, the Notch signaling pathway is essential to promote T cell commitment in the thymus and suppress alternative lineage fate potentials, including B cells, DCs, and myeloid cells [126][127][128]. However, some studies suggest that Notch signaling does not restrict NK cell lineage specification [129][130][131]. In the absence of lineage specifying factors, such as Pax5 in B cells or Bcl11 in T cells, pro-B cells or thymocytes can be reprogrammed into NK cells when cultured with Notch ligands (Bcl11 is a target of Notch1 signaling) [132,133].…”
Section: Notch1 Regulates the Generation Of Hscs And Its Commitment Tmentioning
confidence: 99%
“…In the absence of lineage specifying factors, such as Pax5 in B cells or Bcl11 in T cells, pro-B cells or thymocytes can be reprogrammed into NK cells when cultured with Notch ligands (Bcl11 is a target of Notch1 signaling) [132,133]. Further studies in Vav1-Cre-Rbp-JK fl/fl mice showed that not only is the number of early BM NKPs reduced, but the maturation of splenic NK cells is also blocked [129][130][131]. Rbp-JK is an essential transcriptional effector in the Notch signaling pathway [113].…”
Section: Notch1 Regulates the Generation Of Hscs And Its Commitment Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Collective reports have demonstrated that iNK cells in mouse bone marrow and periphery can express Ly49 receptors, CD49a, CD90, TRAIL, CD69, and Eomes, and lack CD49b expression (3, 21, 2931). Upon adoptive transfer into lymphopenic mice, iNK cells can induce CD49b expression and retain Eomes expression (3).…”
Section: Developmental and Activation States Of Group 1 Ilcsmentioning
confidence: 99%